2018
DOI: 10.1016/j.jpain.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Threat on Pain, Aggression, and Empathy in Women

Abstract: A threatening social context affects how threatening pain is perceived and has interpersonal consequences such as increased aggression and reduced empathy, thereby creating a double burden on the individual suffering from pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 52 publications
1
39
3
Order By: Relevance
“…Pain is a global health problem with broad negative impacts on physical (Sturgeon, Darnall, Kao, & Mackey, 2015; Sturgeon, Dixon, Darnall, & Mackey, 2015), mental (Bair, Robinson, Katon, & Kroenke, 2003; Feinstein et al, 2017; Ziadni, Sturgeon, & Darnall, 2018), spiritual (Halawa, Al-Diri, McLean, & Darnall, 2015), psychosocial (Karos, Meulders, Goubert, & Vlaeyen, 2018; Karos, Williams, Meulders, & Vlaeyen, 2018; Sturgeon et al, 2016; Ziadni, You, Wilson, & Darnall, 2018), and economic domains (Groenewald, Essner, Wright, Fesinmeyer, & Palermo, 2014; Gustavsson et al, 2012). The 2016 Institute of Medicine report on Relieving Pain in America estimated that roughly one-third of the world population is living with ongoing pain of some type (IOM Committee on Advancing Pain Research, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a global health problem with broad negative impacts on physical (Sturgeon, Darnall, Kao, & Mackey, 2015; Sturgeon, Dixon, Darnall, & Mackey, 2015), mental (Bair, Robinson, Katon, & Kroenke, 2003; Feinstein et al, 2017; Ziadni, Sturgeon, & Darnall, 2018), spiritual (Halawa, Al-Diri, McLean, & Darnall, 2015), psychosocial (Karos, Meulders, Goubert, & Vlaeyen, 2018; Karos, Williams, Meulders, & Vlaeyen, 2018; Sturgeon et al, 2016; Ziadni, You, Wilson, & Darnall, 2018), and economic domains (Groenewald, Essner, Wright, Fesinmeyer, & Palermo, 2014; Gustavsson et al, 2012). The 2016 Institute of Medicine report on Relieving Pain in America estimated that roughly one-third of the world population is living with ongoing pain of some type (IOM Committee on Advancing Pain Research, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Second, more research into the modulation of defensive behaviors (e.g., freezing, pain-related avoidance behavior) by social context is warranted. One possibility is the use of more dynamic and ecologically valid social manipulations such as virtual reality, video materials or actual social interactions using confederates ( Karos et al, 2019 ; Karos et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… Peeters & Vlaeyen (2011) found that participants show less painful facial expression when receiving electrical stimuli in a threatening social context, possibly a result of freeze-like reductions of overall body movement. Subsequent attempts to replicate this finding have been mixed ( Karos et al, 2019 ; Karos et al, 2018 ). However, no study to date has investigated the effect of pain on actual body sway and bradycardia, or its modulation by social context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggests that the social context can play an important role. A threatening social context can worsen the experience of painful stimuli [33,38,39], the communication of pain to others [33,34,58], and facilitate the acquisition of pain-related fear [36]. More generally, chronic pain has been associated with a whole host of threatening social experiences such as social isolation and injustice [37].…”
Section: Introductionmentioning
confidence: 99%